DESIGNING FOR EVERYONE: HOW MOTION DESIGN IMPROVES ACCESSIBILITY AND EMOTIONAL INTELLIGENCE - Saniya Assembek (Modern American Journals, 2025)
The article examines the theoretical and practical aspects of using motion design as an effective tool for creating accessible and inclusive digital interfaces. Particular attention is paid to the role of animation in reducing cognitive load, supporting navigation, sensory compensation and ensuring emotional comfort for users with various perception and health features. International accessibility standards, such as WCAG 2.2, are analyzed, as well as examples of successful use of motion design in educational platforms, mental health applications and social projects. The importance of emotional intelligence and visual empathy in digital design for the formation of a human-oriented user experience is emphasized. The results of the study confirm the significant role of motion design in creating universal and adaptive solutions that promote equal participation of all categories of users in the digital environment.
Keywords: motion design, digital accessibility, inclusive design, cognitive load, emotional intelligence, universal design, animation, visual empathy, WCAG 2.2, multimodal interfaces, user experience, digital interfaces, educational technologies, mental health.